Aerodynamics of a car - Yeong, Dun Jie (Nanyang Technological University, 2020)
Modifications on automobiles exist everywhere and they come in a myriad of forms, shapes and sizes. There are those who choose to be practical and opt for modifications that reduce the drag force experienced to reap cost savings from lesser fuel expended. Vortex generator fins are one of the modifications that reduces drag. As the name suggests, its function is to generate vortices and delay the flow from separating at the rear of the automobile to reduce pressure drag. The focus of this project is to enhance the drag reduction capabilities of vortex generator fins. Inspiration was drawn from the Mako shark, which is the fastest shark in the ocean, in using its denticles to design vortex generator fins that can be applied onto automobiles. The designs will be done in SolidWorks to create computer aided design (CAD) models and subsequently tested on an Ahmed Body in ANSYS FLUENT®. The performance of these Mako shark denticle inspired fins will be evaluated in terms of its drag coefficient reduction performance and compared against delta shaped fins, which currently produces the best results. As Mako fins have never been studied with automobiles, it will be optimised in terms of its orientation with respect to the air flow and the number of fins present per orientation. The results will be translated to the cost savings from fuel saved per trip to the petrol kiosk to make relatable sense of it. The simulation results have revealed that as the orientation increasingly deviates away from being aligned to the air flow, the performance worsens. Also, there is no distinct correlation between number of fins and performance for each orientation simulated. The project concludes with the finding that the Mako shark denticle inspired fins performs insignificantly better than the delta shaped fins only at a very specific orientation and with a specific number of fins in that orientation.